THE STRATEGY OF PRINCIPAL IN THE IMPLEMENTATION OF CHARACTER EDUCATION IN SMP MUHAMMADIYAH 1 MEDAN - Selamat Pohan; Frida Yanti Sirait (Proceeding International Seminar of Islamic Studies, 2021)
This study aims to analyze the principal's strategy in implementing character education for students at SMP Muhammadiyah 1 Medan, how the principal's strategy is to apply it. This study uses a descriptive qualitative approach. This research was conducted in 5-6-2020 . The subject of this research is the principal. Data collection was carried out through observation, used for data on students' Muhammadiyah values and morals, interviews were used for data related to efforts regarding strategies for implementing Muhammadiyah and moral education, while documentation was in the form of material programs to complement the results of observations and interviews. The results of this study are as follows. (1). The value of Kemuhammadiyahan lessons and morals that can provide reinforcement to shape the character of students of SMP Muhammadiyah 1 Medan are the demands of the determination of the results of the conference. (2). The strategy taken by the principal in the context of implementing character education is through the application of Mabid (night of worship) once a month. (3). The implementation of character education at SMP Muhammadiyah Medan is something that is familiar for the purpose of managing educational institutions in the Muhammadiyah organization. Keywords: Principal, Character Education, Muhammadiyah Junior High School.